Fluoroscopic Views for a More Accurate Placement of Iliosacral Screws: An Experimental Study. Issue 1 (January 2016) - Kim, Ji Wan; Quispe, Juan C.; Hao, Jiandong; Herbert, Benoit; Hake, Mark; Mauffrey, Cyril
Abstract : Objectives: Misperception on the fluoroscopic image showing a well-placed iliosacral (IS) screw can occur, when the screw is in reality misplaced. The purpose of this study was to demonstrate and highlight examples of misperception and suggest alternative inlet and outlet views to confirm adequate IS screw placement. Methods: We used 9 different pelvic plastic models. In 8 of those models, IS screws were purposely misplaced: exiting anterior at the midportion of the S1 body, exiting at the lateral aspect of the anterior S1 body, abutting posterior to S1 body, exiting posterior to the S1 body, exiting superior to the far-side of the sacral ala, exiting superior to the S1 body, exiting partially in the S1 foramen, exiting completely in the S1 foramen. One model was used as control with correct screw placement. Different outlet and inlet views were tested to accurately detect important anatomic landmarks and avoid fake phenomenon (FP) using 3 different angles. Results: Misperception occurred in 3 models: (1) penetration at the midportion of the anterior border of S1, (2) penetration of the superior sacrum ala, and (3) partial penetration of S1 foramen. In the first situation, misperception could be avoided when the "anterior inlet view" was obtained. In the other 2 situations, misperception could be avoided using specific outlet views herein described. Conclusions: Our findings highlight that misperception can occur using standard inlet and outlet views. We suggest using 2 variations of the inlet views and 3 variations of the outlet views to avoid misperception in clinical practice. Abstract : Supplemental Digital Content is Available in the Text.